Opportunities and Challenges of Public Space Commercialization from Economic Security Perspective - Azizah, Siti; Suyanto, Bagong; Karnaji, Karnaji (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
Abstract The commercialization of public spaces is increasingly common in major cities, transforming areas once open and freely accessible into spaces focused on commercial activities. This shift not only changes the primary role of public spaces as venues for social interaction but also introduces challenges and opportunities for economic security. From an economic security perspective, the commercialization of public spaces offers both benefits and risks for communities and local governments. On one hand, it can stimulate economic growth through increased business activities, job creation, and urban revitalization. On the other hand, it can exacerbate socio-economic inequalities, marginalize vulnerable groups, limit access, and erode the social function of public spaces. This study investigates the impact of public space commercialization on economic security, focusing on how this transformation affects accessibility, economic disparity, and social welfare sustainability. Through literature analysis and case studies, the study provides comprehensive insights into managing public space commercialization sustainably while upholding inclusive and equitable economic security principles. The findings indicate that while commercialization offers economic opportunities, it also heightens social inequality, highlighting the need for inclusive policies to safeguard economic security. These findings aim to guide policymakers in balancing economic interests with the social functions of public spaces, ensuring that policies are inclusive, equitable, and support sustainable economic security for all societal groups